Disparities in adherence to head and neck cancer follow‐up guidelines. (24th December 2018) - Perlow, Haley K.; Ramey, Stephen J.; Cassidy, Vincent; Kwon, Deukwoo; Farnia, Benjamin; Nicolli, Elizabeth; Samuels, Michael A.; Freedman, Laura; Elsayyad, Nagy; Yechieli, Raphael; Samuels, Stuart E.
Abstract : Objectives: In this study, we aim to determine the frequency of adherence to National Comprehensive Cancer Network follow‐up guidelines in a population of head and neck cancer patients who received curative treatment. We will also assess the impact of race, ethnicity, socioeconomic status, and treatment setting on utilization of follow‐up care. Methods: This study included patients with biopsy‐proven, nonmetastatic oropharyngeal or laryngeal cancer treated with radiotherapy between January 1, 2014, and June 30, 2016, at a safety‐net hospital or adjacent private academic hospital. Components of follow‐up care analyzed included an appointment with a surgeon or radiation oncologist within 3 months and posttreatment imaging of the primary site within 6 months. Univariable and multivariable analyses were conducted using a logistic regression model to estimate odds ratios and corresponding 95% confidence intervals. Results: Two hundred and thirty‐four patients were included in this study. Of those, 88.8% received posttreatment imaging of the primary site within 6 months; 88.5% attended a follow‐up appointment with a radiation oncologist within 3 months; and 71.1% of patients attended a follow‐up appointment with a surgeon within 3 months. On multivariable analysis, private academic hospital treatment versus safety‐net hospital treatment was associated with increased utilization of both surgical and radiation oncology follow‐up. Non‐Hispanic black (NHB) patients, Hispanic patients, and those with a low socioeconomic status were also less likely to receive follow‐up. Conclusion: Safety‐net hospital treatment, socioeconomic status, Hispanic ethnicity, and NHB race were associated with decreased follow‐up service utilization. Quality improvement initiatives are needed to reduce these disparities. Level of Evidence: 2b Laryngoscope, 129:2303–2308, 2019